The law of gradual growth: understanding how time affects your spiritual maturity - Meyer,Joyce (Tulsa, Okla: Harrison House, 2010)
In this liberating message, you'll learn what the law of gradual growth is and how it applies to your Christian walk. You'll also discover the difference between living in your own strength and God's strength and why it is so important to read the Bible as a promise from God and not a law.